Land use influence on biodiversity and activity patterns of predators and prey in the semi-arid drylands of South Africa - Ayinla, Oluwaseun (Department of Biological Sciences, 2024)
The unprecedented rise in anthropogenic activity worldwide has left wildlife with no other choice but to find means to coexist with humans across a range of different land uses. While some animals have developed strategies to adapt to the gradual and long-term modifications to the environment as a result of anthropogenic disruptions, rapid and pervasive changes often result in drastic reduction in species abundance causing local extirpation and posing a threat to ecosystem sustainability. Some behaviourally plastic species may be able to cope in real time to changes brought about by anthropogenic disruptions in their habitat, but they may have to compete with humans directly for space and food prompting negative interactions between people and wildlife which in turn lead to conflicts between conservation bodies on how best to mitigate these interactions. Understanding these interactions and how they influence ecosystem level functions, community interactions and the long-term persistence of wildlife is essential to achieving biodiversity goals. Most studies on wildlife in South Africa have focussed on protected areas but given that most animals still persist outside protected areas, it is imperative to expand research to include human modified landscapes too. The goal of my study was to 1) explore how wildlife adjust their activity with land use and, 2) determine whether heavily persecuted species adjust their activity more in human modified landscapes compared to protected areas and 3) how prey species adjust their activity with and without apex predators and 4) whether lunar illumination influences the activity of heavily persecuted species on farmland and predator-prey interactions in protected areas. I used camera trap surveys conducted on farmland between September 2012 and March 2013, in Anysberg Nature Reserve between the end of September 2013 and May 2014 and in Sanbona Wildlife Reserve between the end of August and November 2015 to provide insights into the relationships between land use, biodiversity, and predator-prey dynamics in the semi-arid drylands of South Africa. My study showed that semi-arid drylands of South Africa are important refugia for wildlife which is evident in the high species richness found in my study. I found that the temporal overlap for the same species living in Anysberg Nature Reserve and the nearby small livestock commercial farmland of Koup were not dissimilar. However, heavily persecuted (e.g., black backed jackal) and harvested species (e.g., steenbok) exhibited greater nocturnality on farmland presumably to avoid the diurnal peaks in farm worker activity. The presence and absence of apex predators had minimal influence on the activity of both smaller predators and a large size range of potential prey. That said both plains zebra and kudu showed increased nocturnal behaviour in the absence of lion which typically hunt at night. The response of wildlife to moon phase in different land uses was mixed with no clear patterns in the proportion of activity at night with different moon phases in either Anysberg or the farmland. This dissertation highlights the complex interplay between human activities and wildlife populations and provides important baseline information on the relationships between land use, biodiversity, and predator-prey dynamics that can be used to explore future shifts in both land use and climate in the drylands of the Karoo.